On temporality and the culture of work in young cooperative members: Rethinking forms of connection with collective work - Otero, Analia Elizabeth; Fernández, Facundo; Gragnolati, Andrés (Cooperativismo & Desarrollo, 2021)
Problems related to the labor insertion of the young population sector are already a topical part of current research and policies that continue to gain weight in a context of low economic growth. The magnitude of these confronts us with the challenge of reflecting extensively on the relationship of young people with productive and labor activity. Along these lines, we focus here on a variant that escapes typical dependent employment, addressing the relationship between youth and cooperativism. More specifically, the objective of this article is to present findings from an investigation on young people and cooperativism, focusing on problems related to the culture of work and the conceptualization of time in them. Reflects on the notion of work culture in cooperative forms of work and, in connection with it, the tension between work time - leisure time. As part of the findings, it is understood that the values ​​of cooperativism are fundamental to understand the culture of work and temporality as a longitudinal dimension that crosses various spheres.